A promising drug delivery candidate (CS-g-PMDA-CYS-fused gold nanoparticles) for inhibition of multidrug-resistant uropathogenic Serratia marcescens. (1st January 2020) - Shi, Ping; Amarnath Praphakar, Rajendran; Deepa, Sadhasivan; Suganya, Kannan; Gupta, Prashant; Ullah, Riaz; Bari, Ahmed; Murugan, Marudhamuthu; Rajan, Mariappan
Abstract: Antibiotic resistance amongst microbial pathogens is a mounting serious issue in researchers and physicians. Various alternatives to overcome the multidrug-resistant bacterial infections are under search, and biofilm growth inhibition is one of them. In this investigation, a polymeric drug delivery system loaded with multi-serratial drugs to improve the delivery of drugs against urinary tract infection causative Serratia marcescens . The chitosan grafted pyromellitic dianhydride – cysteine (CS-g-PMDA-CYS) was conjugated with AuNPs by using the –SH group of CYS and RF (rifampicin) and INH (isoniazid) were loaded in AuNPs-fused CS-g-PMDA-CYS system. Several physicochemical techniques characterized this fabricated AuNPs/RF/INH/CS-g-PMDA-CYS system. The successful encapsulation of RF and INH in AuNPs-fused CS-g-PMDA-CYS polymer had confirmed, and it observed the loading capacity for RF and INH was 9.02% and 13.12%, respectively. The in vitro drug discharge pattern was perceived high in pH 5.5 compared with pH 7.4. The AuNPs/RF/INH/CS-g-PMDA-CYS escalates 74% of Caenorhabditis elegans survival during Serratia marcescens infection by aiming biofilm development and virulence in S. marcescens . Author postulate that the fabricated system is a promising drug carrier and delivery system for inhibition of multidrug-resistant bacterias like S. marcescens .